Optimization Of Law Enforcement Against Tax Crimes In Indonesia - Nur, Fuad (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to identify and analyze the factors influencing the enforcement of criminal law in the field of taxation and the efforts that can be made to optimize law enforcement in the field of taxation. The research method used is normative juridical research utilizing secondary data. Data collection techniques involve library study analyzed qualitatively. The research findings indicate that the factors influencing law enforcement in the field of taxation are legal factors, law enforcement officer factors, means or facilities factors, and societal factors. Furthermore, to optimize law enforcement in the field of taxation, it requires collaborative strengthening between institutions and the effectiveness of the tax judiciary system. Law enforcement is not only limited to the fulfillment of law enforcement officers resources but also requires cooperation between law enforcement agencies and other institutions amidst the complexity of tax evasion schemes with various modes of operation. In addition, the tax justice system also plays a crucial role in deterring taxpayers who commit violations. Criminal prosecution is pursued as a response and last resort due to the taxpayer's failure to fulfill all their obligations. Therefore, optimal law enforcement will create a deterrent effect for tax offenders, increase taxpayer compliance, and ultimately boost state revenue.